Complex Effects of Free Stream Turbulence and Surface Roughness on the Transitional Intermittency - Hladik, Ondrej; Jonas, Pavel; Mazur, Oton; Uruba, Vaclav (Communications - Scientific letters of the University of Zilina, 2012)
The comparison of transitional intermittency distributions in boundary layers on smooth and rough surface is presented. The conditional analysis of the instantaneous wall friction is applied on time records made in transitional boundary layers originating on smooth surface or surface covered by sand paper. Special procedures of measurement and evaluation are applied that allowed evaluations of turbulent and nonturbulent zone averages.